Mineral and Coal Mining Business and Management in Indonesia from the Indonesian Constitutional Viewpoint - Ferdiansyah Agustinus, Ivan (Journal of World Science, 2022)
Mineral and coal wealth in Indonesia has long been exploited and exploited since before Indonesia's independence. The mineral and coal management and exploitation scheme has undergone changes starting from using the Contract of Work/Agreement of Work scheme to using the Mining Business Permit scheme, all of which are claimed in accordance with Article 33 paragraph (3) of the NRI Constitution as the Indonesian constitution. The research aims to look at the management and exploitation of mineral and coal mining in Indonesia from the point of view of the 1945 Constitution of the Republic of Indonesia. The research method used in this paper is a normative research method, emphasizing the use of secondary data, namely examining the principles of law and legislation. invitations, which are sourced from primary legal materials, secondary legal materials and tertiary legal materials. In this study, it was concluded that the 1945 Constitution of the Republic of Indonesia mandates that the management and exploitation of mineral and coal mining by the Government must have a dominant role, the role of the government is not only to regulate, manage and supervise but also plays a role in its management as interpreted by the Constitutional Court's decision. Number 111/PUU- XIII/2015 and the ideas of Moh. Hatta, it does not mean that the Indonesian people reject foreign investment, but that there is a need for a new scheme, one of which is a Joint Venture where 51% or more of the shares are owned by the government or its representatives.